Eating behaviors and liver health in metabolic dysfunction-associated fatty liver disease: the serial mediating roles of Mediterranean diet adherence and adiposity - Başar Gökcen, Büşra; Kurtuluş, İrem; Kabak, Nermin; Budan, Ferenc; Ağagündüz, Duygu; Szép, Dávid (Frontiers in Nutrition, 2026)
BackgroundThis study aimed to investigate the mediating roles of healthy diet adherence and adiposity in the relationship between eating behaviors (uncontrolled or mindful eating) and liver health according to metabolic dysfunction-associated fatty liver disease (MALFD) status.MethodsAdults with and without MAFLD (150 and 90, respectively) were included. Eating behaviors were assessed using the Mindful Eating Questionnaire (MEQ) and Three-Factor Eating Questionnaire (TFEQ), and Mediterranean diet adherence was measured with the Mediterranean Diet Adherence Screener (MEDAS). Adiposity indices included Body Mass Index (BMI) and Visceral Adiposity Index (VAI). Liver health markers were alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Statistical analyses comprised group comparisons, Spearman correlations, and serial mediation models tested using Hayes’ PROCESS macro.ResultsIndividuals with MAFLD had higher BMI (median 32 vs. 25 kg/m2), VAI (4.1 vs. 1.1), and ALT levels (83 vs. 20 U/L, all p < 0.001). In unadjusted comparisons, the MAFLD group showed lower MEQ and MEDAS scores, together with higher emotional eating and uncontrolled eating scores on the TFEQ. In multivariable logistic regression analyses, BMI was independently associated with MAFLD status (OR = 1.43, 95% CI: 1.30–1.57), while eating behavior scores were not significant after BMI adjustment. Serial mediation analyses using PROCESS Model 6 showed that the association between uncontrolled eating scores and ALT levels was indirectly transmitted through BMI, with the serial indirect pathway involving MEDAS and BMI reaching statistical significance in the MAFLD group (indirect effect = 0.106; 95% bootstrap CI: 0.019–0.251). Moderated mediation analyses using PROCESS Model 92 further indicated a significant index of moderated mediation for this pathway (IMM = 0.090; 95% bootstrap CI: 0.003–0.233), whereas mediation models based on mindful eating scores did not yield significant moderated mediation effects.ConclusionThe results support the presence of indirect associations linking eating behavior scores to liver enzyme levels via Mediterranean diet adherence and adiposity, particularly in the context of MAFLD. These pathways point to potentially modifiable behavioral and dietary targets, while underscoring the need for confirmation through prospective and interventional studies.